Design and Development of a Drinking Water Dispensing System with Volume Control Based on IoT for The Elderly - Syahputra, Luthfi Adi; Kusumawardani, Mila; Suharto, Nugroho (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
The issue of adequate water intake becomes increasingly relevant for the elderly who experience a decline in motor function, often leading to difficulties in pouring water accurately. This can result in spills or inaccurate filling, potentially compromising their daily hydration needs. Therefore, this research focuses on the design and development of an automatic water dispenser system to assist the elderly in meeting their hydration needs. The proposed system utilizes the HC-SR04 sensor to detect the water container’s height, the XKC-Y25-V sensor to measure the water filling level, and Firebase as a storage medium for user water quota data. The testing results show that the water filling rate reaches 35 ml per second, with a filling error rate of 23.15% at a sensor height of 7 cm and 15% at a sensor height of 14 cm. Additionally, the NFC reader sensor demonstrates 100% accuracy with a maximum detection range of 3 cm. Ultrasonic sensor data indicates a reading difference of 13.6% longer for the sensor positioned at a height of 7 cm, and -3.6% shorter for the sensor at a height of 14 cm, with a 100% object detection success rate. The water sensor records a value of 0 when no water is being poured and a value of 1 when water filling is in progress.